(untitled) (E Global Congress, 2024)
The article analyzes the psychologism through the intricate development of characters Louisa Clark and Will Trainor. Louisa transitions from a directionless individual to someone ignited by ambition and growth, catalyzed by her interactions with Will. Conversely, Will grapples with despair and a profound identity crisis following his paralysis, illuminating themes of autonomy and the psychological impacts of disability.